PROBLEMS OF REGIONAL DEVELOPMENT AND REGIONAL ECONOMY OF BULGARIA.FEATURES AND APPLIED ASPECTS - Petrov , Kamen; Stoyanova, Milena (Revista Inclusiones, 2020)
The objectof the study is regional development planning. In this territory, smaller administrative unitsof different ranks have formed; we study their structure and behavior as a prerequisite to understand the core of their vital activity designed mainly through their development and regional development. These distinct areas in our country are the subject of our research as well as ensuing problems with their administrative spatial planning and overall implementation of policies for regional development. In this direction, the purpose of our study is to highlight those processes of regionalization that could promote regional development policies and, secondly, to show deficits accumulated by the tradition of the structure and the management of regional communities in Bulgaria.